Chenopodium ambrosioides L.: estudo etnofarmacológico no bairro do Maracanã, São Luís, Maranhão. - SILVA, Geraldo Mendonça (2012)
Chenopodium ambrosioides L. (Chenopodiaceae), common name: mastruz, represents a vegetable species of great importance in Maranhão state and widely used in popular practice, specially therapeutics. This essay means to do an ethnopharmacological study on dwellers from Maracanã neighborhood, São Luís, Maranhão, with emphasis in Chenopodium ambrosioides L. use, rescue the awareness of medicinal plants using by the population on study, investigate the popular application of the plant species, identify form and finality of Chenopodium ambrosioides usage and compare the therapeutics properties popular information awarded to the vegetable species of the scientific data. As methodological procedure, a semi-structured questionnaire was used, containing open and closed questions, applied on Maracanã neighborhood dwellers from May to June of 2011. The sample was formed by one hundred and five dwellers, eighty-three women and twenty-two men, being preferably interviewed the oldest dweller in the households. The women were more acquainted with the plants as therapeutic alternative. Most of the users were between fifty-six and sixty-five years old, have studied between one and nine years, with an income of one to five minimum wages, catholics and crossbreeds. Forty-four vegetable species were reported by the common name, being them boldo (Peumus boldus Molina, Vernonia condensata Beker), mint (Mentha piperita L.), balm (Lippia alba (Mill) N. E.) and the mastruz (Chenopodium ambrosioides L.) the four most quoted in order, and in major part, coming from home cultivation. From mastruz, the most used part was the leaves and, preferably, the younger ones. The processing most used by the population, was maceration, with water. The principal mastruz usage was as anti-inflammatory, mainly managed by oral via, from one to two cups a day, for at least one week. There weren't any toxicity occurrences. Most of the interviewed people has shown satisfaction with the treatment, using the vegetable species and recommending its usage.